CHECKING SIMILARITY IN EFL UNDERGRADUATE STUDENTS’ RESEARCH PROPOSAL - I Gede Yoga Permana (Universitas Pendidikan Ganesha, 2022)
The current study aimed at identifying the similarity found in undergraduate students’ research working paper. In doing similarity check, a software named Plagiarism X checker was used. A hundred students’ research paper were collected and similarity checked. The result showed that the similarity identified in students work is 22.18% which falls into medium category. The highest percentage of similarity is found in the background of study (13.86%) followed with theoretical review (5.22%) and research method (3.08%). In background of study, the highest percentage of similarity is 34% that belongs to medium level. Meanwhile in theoretical review and research method the similarity is less than 15% that indicates a small level. Some papers were identified contain a stolen paragraph because the use of exact same words with the original sources without any process of editing. Discussion and suggestions are further presented.